2012
DOI: 10.1128/aem.00400-12
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Degradation of 2,4-Dichlorophenoxyacetic Acid on the Greenland Ice Sheet

Abstract: ABSTRACTThe Greenland ice sheet (GrIS) receives organic carbon (OC) of anthropogenic origin, including pesticides, from the atmosphere and/or local sources, and the fate of these compounds in the ice is currently unknown. The ability of supraglacial heterotrophic microbes to mineralize different types of OC is likely a significant factor determining the fate of anthropogenic OC on the ice sheet. Here we determine the potential of the microbial community from the surface of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…In contrast, previous studies imply that respiration in cryoconite might resist environmental disturbances in the interior zones of the Greenland Ice Sheet. There, the dominant heterotrophs are metabolically flexible (White et al, 1996;Stibal et al, 2015) and unlikely to be limited by contemporary autochthonous OC production (Stibal et al, 2010;2012b;Telling et al, 2012). Our data cannot be used to determine rates of photosynthesis and respiration individually because the artificial manipulation of light regime in our experiments weakens the assumption of parity between respiration in light and dark incubations (e.g.…”
Section: Implications For Glacier Ecology and Biogeochemistrymentioning
confidence: 88%
“…In contrast, previous studies imply that respiration in cryoconite might resist environmental disturbances in the interior zones of the Greenland Ice Sheet. There, the dominant heterotrophs are metabolically flexible (White et al, 1996;Stibal et al, 2015) and unlikely to be limited by contemporary autochthonous OC production (Stibal et al, 2010;2012b;Telling et al, 2012). Our data cannot be used to determine rates of photosynthesis and respiration individually because the artificial manipulation of light regime in our experiments weakens the assumption of parity between respiration in light and dark incubations (e.g.…”
Section: Implications For Glacier Ecology and Biogeochemistrymentioning
confidence: 88%
“…Numerous genes detected in glacier ice core metagenomes related to xenobiotics, biopolymers and other carbon sources suggest that glacial ice microorganisms have the potential to degrade a wide range of substrates [17]. Microbial degradation of xenobiotic compounds from distant allochtonous sources has been observed on the Greenland ice sheet [91]. Microbial preferences for different carbon classes were also studied in Antarctic snow and results showed a higher rate of carbon uptake when snow microcosms were amended with a combination of simple and complex carbon sources [92].…”
Section: High Light Radiation and Low Nutrient Concentrationsmentioning
confidence: 99%
“…It is now known that about half of the world's freshwater bacterial biomass is present within the world's glaciers and ice sheets, and that these environments represent active ecosystems in their own right . However, while the role of microbes in the bioremediation of contaminants in polluted soils and sediments is well known, it has been almost completely overlooked in the case of glacial ecosystems . The role of biofilms in glacial contaminant dynamics therefore requires quantitative treatment for the first time.…”
Section: State Of the Sciencementioning
confidence: 99%
“…42 However, while the role of microbes in the bioremediation of contaminants in polluted soils and sediments is well known, it has been almost completely overlooked in the case of glacial ecosystems. 43 The role of biofilms in glacial contaminant dynamics therefore requires quantitative treatment for the first time. Recent research has demonstrated how biofilm-type microbial ecosystems thrive upon glaciers when they melt, producing aggregates of mineral and anthropogenic particulates encapsulated by extracellular polymeric substances (EPS) that are exuded by very active cyanobacteria and other microorganisms 36,44 (Figure 1).…”
Section: Bioflocculation and Biodegradation: Hitherto Overlooked Contmentioning
confidence: 99%